Integrated and eco-friendly management of powdery mildew disease in commercial viticulture - M, Ramya Sree; Singh, Sanjay K; Prakash, Jai; Kumar, Chavlesh; P, Roshni; Amala, Ediga (Indian Horticulture, 2024)
Grapevine is one of the major fruit crops grown worldwide. In India, the major grape-growing states are Maharashtra, Karnataka, Tamil Nadu, and Mizoram. The production of grapes is limited due to several pests and diseases infestations among which powdery mildew is the second most important endemic disease, causing huge economic losses, i.e., upto 40% reduction in yield every year. Atpresent, its management is largely dependent upon the use of chemical fungicides. The best alternative strategy is by using eco-friendly management practices to reduce crop loss and disease severity. The integrated disease management (IDM) modules are the other safe options that need to be popularized amongst growers for producing residue-free grapes that would fetch higher market price and also boost the export.